Glucose restriction reverses the Warburg effect and modulates PKM2 and mTOR expression in breast cancer cell lines - Tahtouh, Roula; Wardi, Layal; Sarkis, Riad; Hachem, Ray; Raad, Issam; El Zein, Nabil; Hilal, George (Cellular and Molecular Biology, 2019)
Aerobic glycolysis, known as the "Warburg effect”, is one of several hallmarks of cancer cells. The conversion of phosphoenolpyruvate (PEP) to pyruvate can be down regulated by the re-expression of the embryonic isoform 2 of pyruvate kinase (PKM2). This mechanism allows the accumulation of glycolytic intermediates for the biosynthesis of macromolecules, such as proteins, lipids and nucleic acids. PKM2 is favored by the well-known PI3K/Akt/mTOR proliferative pathway. This pathway is induced by high glucose levels, and the mTOR kinase is the central activator of the Warburg effect. In this study, we investigated the role of glucose restriction (GR) and mTOR inhibition in reversing the Warburg effect in MDA-MB 231 and MCF-7 breast cancer cell lines. PKM2 expression was measured by western blot. Lactate production by cells was determined by a colorimetric assay. The concentration of glucose in the supernatant of cells was measured using the Trinder method. ATP level was evaluated by using a Colorimetric/Fluorometric ATP Assay Kit. Our results showed that MDA-MB 231 cells increased glucose consumption when the glucose concentration was 0 g/L (P <0.01). In MCF-7 cells, glucose deprivation reduced lactate secretion by 80% (P =0.0001) but tripled glucose consumption (P = 0.0041). ATP concentration increased approximately when MCF-7 cells were deprived of glucose (P = 0.02). GSK1059615 does not significantly modulate lactate secretion and glucose uptake in both cell lines. Glucose restriction contribute to the reduction of the Warburg effect through mTOR inhibition and regulation of PKM2 kinases.